An Elderly Female with Pulmonary Oedema Manifestation of Dengue Hemorrhagic Fever : a Case Report - Gunawan, Mikhael Fabian; Sjam, Mohammad Bhukkar Adil; Miranda, Adriana Viola (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Dengue Hemorrhagic Fever (DHF) is an arthropod borne viral disease. The main vector of the disease are the Aedes mosquitoes. Indonesia as one of the tropical nations in South Asia falls into one of the countries in which DHF is an endemic. The notable clinical symptoms are fever usually 400c with a biphasic pattern in 6% of DHF cases, body ache, muscles, retroorbital and joints, nausea, and vomiting. Fluid accumulation, due to plasma leakage, may occur in the abdominal cavities, pleural space, and even the lungs. The rise of non-communicable diseases like diabetes mellitus has impacted the clinical progression of DHF by increasing the risk of developing into dengue shock syndrome and atypical clinical manifestation of dengue plasma leakage and bleeding disorder. This case report discusses one of these atypical clinical manifestations of DHF. The case is an elderly female presenting in the emergency room with a DHF, Diabetes mellitus type 2, cardiomegaly, and during inpatient care developed a pulmonary Oedema. The patient experienced prolonged fever and on the 7th day of care develops a pulmonary oedema, the patient is then moved to the intensive care unit, and with proper treatment and monitoring was able to recover from the disease